PERAN KEBIJAKAN PRESIDENSI G20 INDONESIA TAHUN 2022 DALAM TRANSFORMASI PERDAGANGAN INTERNASIONAL - Maharani Agustin; Silla Anbiya; Elsa Putri Rahmadini (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
In facing the complex dynamics of international trade in 2022, the policies implemented by the G20 Presidency of Indonesia played a central role in reshaping the global trade paradigm. This research explores, analyzes, and evaluates this role using a qualitative approach and literature review. The strategic policies formulated by the G20 Presidency of Indonesia not only reflect responses to global trade challenges but also aim to steer positive transformation within the framework of international trade. Through qualitative analysis, this study depicts diverse stakeholder perspectives regarding the implementation of these policies, while exploring their implications and impacts on global trade dynamics. A literature review approach is employed to detail and identify the background, concepts, and recent developments in global trade policies, forming a profound understanding of the G20 Indonesia's role in this transformative process. The results of this research provide comprehensive insights into how the policies of the G20 Presidency of Indonesia in 2022 significantly contribute to the evolution of international trade and simultaneously add to the body of literature on global trade policies.